Fatherhood in the Verses of the Qur'an - Siti Shofiyah; Syarah Sofiah Arifin; Eni Zulaiha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Today, the role of fathers in raising children is a frequently discussed issue. In patriarchal cultures, fathers serve as breadwinners to meet the family's needs. Meanwhile, mothers play a larger role in childcare and household management. This contrasts with the ideal, where fathers, as heads of families, also play a significant role in childcare. Therefore, the phenomenon of fatherhood is important to study and research in greater depth, especially from the perspectives of gender-biased and gender-just commentators. The purpose of this study is to analyze the pattern of fatherhood in the Qur'an and to reveal the views of gender-biased and gender-just commentators on fatherhood. This research method uses a qualitative approach, utilizing a literature review to collect data. This research shows several results including the following; 1) fatherhood has the meaning as the role, function, condition and time of a person becoming a father. 2) in general, scholars of gender bias interpretation argue that the father has a role as a breadwinner and provider in the family, while according to scholars of gender fair interpretation the father has the same role as the mother in terms of caring for and educating children. 3) with gender analysis, it can be seen that the interpretation carried out by scholars of gender fair regarding fatherhood has reflected the spirit of tauhidullah and fulfilled the objectives of the five maqashid sharia, namely maintaining reason (hifz al-aql), maintaining oneself (hifzl an-nafs), maintaining offspring (hifz an-nasl), maintaining property (hifz al-maal) and maintaining religion (hifz ad-din).